2022
DOI: 10.3389/fimmu.2022.818893
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Transcriptome Profiling Reveals a Role for Thioredoxin During Tumor Initiation

Abstract: Neutrophils in the tumor microenvironment exhibit altered functions. However, the changes in neutrophil behavior during tumor initiation remain unclear. Here we used Translating Ribosomal Affinity Purification (TRAP) and RNA sequencing to identify neutrophil, macrophage and transformed epithelial cell transcriptional changes induced by oncogenic RasG12V in larval zebrafish. We found that transformed epithelial cells and neutrophils, but not macrophages, had significant changes in gene expression in larval zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(66 reference statements)
2
1
0
Order By: Relevance
“…By contrast, H 2 O 2 remained restricted to the wound edge in larvae burned in the presence of isotonic solution, displaying a similar localized pattern to that observed after mechanical injury ( Fig. 5F ) 53,57 . Quantification revealed that H 2 O 2 level at the wound edge was similar between control and isotonic treated larvae 6 hpb.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…By contrast, H 2 O 2 remained restricted to the wound edge in larvae burned in the presence of isotonic solution, displaying a similar localized pattern to that observed after mechanical injury ( Fig. 5F ) 53,57 . Quantification revealed that H 2 O 2 level at the wound edge was similar between control and isotonic treated larvae 6 hpb.…”
Section: Resultssupporting
confidence: 63%
“…At 6 hours post burn, H 2 O 2 production was no longer localized to the wound edge in control burned larvae and had increased throughout the tailfin. By contrast, H 2 O 2 remained restricted to the wound edge in larvae burned in the presence of isotonic solution, displaying a similar localized pattern to that observed after mechanical injury (Figure 5F) (Jelcic et al, 2019; Korte et al, 2022). Quantification revealed that H 2 O 2 level at the wound edge was similar between control and isotonic treated larvae 6 hpw.…”
Section: Resultssupporting
confidence: 59%
“…Increased recruitment of immune cells can promote cancer cell progression and metastasis [30, 31]. Larval zebrafish have an intact innate immune system which can be live imaged to evaluate immune cell infiltration and association with tumor cells [27, 32]. Using fluorescent reporters for neutrophils and macrophages, we imaged innate immune cell recruitment to the injection site.…”
Section: Resultsmentioning
confidence: 99%